Innesti e ibridazione tra spazi culturali - Both, Ioana; Saracgil, Ayse; Tarantino, Angela (Strumenti per la didattica e la ricerca, 2015)
This volume collects the interventions of the post-doctoral fellows and PhD students of the Babes Bolyai University of Cluj Napoca, the University of Bucharest and the University of Florence (Doctorate in Mediterranean Languages and Cultures; Doctoral School of Comparative Languages, Literatures and Cultures, specialisation in Language, Literature, Philology: Intercultural Perspectives) presented at the seminar "Innesti e ibridazioni tra spazi culturali" (Florence, 22nd and 23rd November 2012). The contributions focus on the idea of literary and cultural hybridizations between different geographies. Some contributions, in particular those by the Romanian authors, account for the most problematic aspects of the contemporary world using interdisciplinary approaches. The cover image is a work by Judit Kepes, whom we thank for granting us the use of the picture.